Views of Intern Doctors and Clinical Medical Teachers on the achievement of selected objectives of MBBS curriculum-2002 in Bangladesh (Bangladesh Journal of Medical Education, 2019)
Background: A competence based and community oriented with reflection of integrated and community based curriculum was introduced in 2002. Objectives: To assess the achievement of objectives of MBBS curriculum-2002 by the Intern Doctors and Clinical Medical Teachers view in Bangladesh.Materials and Methods: This descriptive cross sectional study surveyed on the performance of Intern Doctors about 60- attributes of clinical and generic skills.Results: The overall result revealed that the Interns' could achieve these skills just below the level of an expected standard. The low performance was observed in certain clinical, procedural and management skills like examination of eye, ear, per rectum examination, auscultation of heart and lung, lumber puncture, fluid aspiration, basic CPR, skin sensitivity test, ante natal check-up and conduction of normal labour, systematic interpretation of basic ECG etc. Though few Interns perceived to have attained mastery in some clinical skills but on the other hand 5-10% of other fellows did not even try the skill during the tenure.Conclusion: All learning must occur in an appropriate clinical context and there should be a system of skill assessment for the Interns.Bangladesh Journal of Medical Education Vol.10(1) 2019: 30-33